Presentation and outcomes in hypertrophic pyloric stenosis: An 11‐year review. (24th January 2019) - Vinycomb, Toby I; Laslett, Kirby; Gwini, Stella M; Teague, Warwick; Nataraja, Ramesh M
Abstract : Aim: To evaluate the trend in presentation and postoperative outcomes of infants with hypertrophic pyloric stenosis (HPS) over the last decade. Methods: This was a multicentre retrospective study in two tertiary paediatric centres between 2005 and 2015 inclusive. Participants included 626 infants who underwent a pyloromyotomy for HPS. We collected data on presentation features (age, weight, clinical signs, blood gas results, ultrasound findings) and postoperative outcomes (length of stay (LOS), complications, time to first postoperative feed). Results: No trend was identified during the study period with regards to age, weight, biochemical findings (pH, chloride, base excess) or pre‐operative ultrasound measurements. There was a downtrend in the number of palpated tumours over time, with a mean of 36% of tumours clinically palpated. Pyloric wall thickness had a moderate association with LOS in patients admitted for >8 days (correlation = 0.4752) but had a weak negative association with shorter lengths of stay (≤8 day, correlation = −0.094). Overall, median time to first feed was 7.80 h and improved yearly during the study period (hazard ratio = 1.07). Conclusions: Patients presenting with HPS are not being identified at an earlier age or with fewer biochemical derangements, in contrast to our initial perceptions. Subsequently, biochemical derangements can still play an important role in the diagnosis of HPS, and attention needs to be given to fluid management and electrolyte correction in all patients with HPS.